Analysis of music influence on order preference based on TOPSIS algorithm. Issue 1 (June 2021) - Liu, Huijiang; Qian, Ziyun; Shao, Jia
Abstract: Music, as a cultural treasure, is currently difficult to accurately measure its influence due to its special nature. In order to solve this problem, an evaluation model based on TOPSIS is proposed. The influence of music is defined as the combination of the number of followers and the number of followers of the same genre as the influencer, and then the TOPSIS method is used to quantitatively analyze the influence of music. By establishing the original data matrix of relevant music characteristics, and then forward and normalize the data matrix, calculate the distance between the data and the optimal solution and the worst solution, and obtain the quantitative score of the music influence value, a right Accurate measurement of music influence is realized.